The comprehensive rural development programme and job creation in Impumelelo - Chidzewere, Previlage (My University, 2016)
With the advent of President Zuma’s administration, the issue of rural development became one of the key focal areas in South Africa (2009-2014). This is also premised in the South African Constitution (Constitution of the Republic of South Africa of 1996) which provides for planning, coordination and implementation of development (rural development included) as one of the key foundations of a developmental state that South Africa envisages. Previous research found that the poorest people in South Africa live in the rural areas where they are still poor, disempowered, characterised with high dependency and outmigration of the economically active. This research used a mixed method approach where quantitative and qualitative questionnaires were used to collect primary data from 50 heads of household in Impumelelo. It was found that the Impumelelo heads of household generally hold positive perceptions on whether service delivery has improved in Impumelelo since the introduction of Comprehensive Rural Development Programme. However, there has been mixed reactions on whether locals have had access to jobs locally and on the issue of skills development for the youth. The majority of Impumelelo heads of household hold negative perceptions on whether Comprehensive Rural Development Programme has been beneficial to women empowerment, youth empowerment and long term employment in Impumelelo.
Keywords: Rural development--South Africa; Economic development projects--South Africa; Poverty--South Africa; Job creation--South Africa